Current Issues of Recodification of Civil Legislation of Ukraine in the Context of European Integration Processese - Сафончик, Оксана Іванівна; Сафончик, О. І.; Сафончик, Оксана Ивановна; Safonchyk, Oksana I.; Глиняна, Катерина Михайлівна; Глиняна, К. М.; Глиняная, Екатерина Михайловна; Hlyniana, Kateryna M.; Еннан, Руслан Євгенович; Еннан, Р. Є.; Эннан, Руслан Евгеньевич; Ennan, Ruslan Ye. (Editorial Primmate S. A. S., 2020)
Civil law plays an important social role, namely, the regulation of property and personal non-property relations, which all members of society are without exception. The Civil Code is often called the economic constitution of the state. Accordingly, the quality of civil law ultimately depends on the well-being of each individual. In addition, the improvement of the current legislation of Ukraine is a prerequisite for deepening the integration processes with the European Community. Thus, timely alignment of current legislation with current realities, part of which is the recoding of civil law, is certainly an important function of every state. The object of the study is the public relations that arise in connection with the recoding of civil law. The subject of the study was the normative acts of Ukraine, international normative acts, civil law doctrine. Scientific research methods such as analysis method, synthesis method, induction methods, and deduction method, and special-legal research methods, such as legal-dogmatic method and method of interpretation of legal norms, were used for the study. It can be conclude that Articles 387 and 391 of the Civil Code of Ukraine should be supplemented by the notions of the vindication and negatoria claims. In addition, there is a problem of competition vindication, restitution and condictia in Art. 1212 of the Civil Code of Ukraine. Secondly, the mechanism for transferring the rights and obligations of the buyer should be more explicit. Thirdly, there is a need to improve the statute of limitations according to the civil law of Ukraine.

Актуальність дослідження не викликає сумнівів, адже цивільне законодавство виконує дуже важливу соціальну роль, а саме – регулювання майнових і особистих немайнових відносин, учасниками яких є всі без винятку члени суспільства. Цивільний кодекс часто називають економічної конституцією держави. Відповідно, від якісного цивільного законодавства у кінцевому рахунку залежить добробут кожної людини. Крім того, удосконалення чинного законодавства України є обов’язковою передумовою поглиблення інтеграційних процесів з Європейським співтовариством. Таким чином, своєчасне приведення чинного законодавства у відповідність із реаліями поточного моменту, частиною якої є рекодифікація цивільного законодавства є, безумовно, важливою функцією кожної держави.Об’єктом дослідження є суспільні відносини, які виникають у зв’язку з рекодифікацією цивільного законодавства. Безпосереднім об’єктом дослідження стали нормативно-правові акти України, міжнародні нормативно-правові акти, цивільно-правова доктрина.Для здійснення дослідження були використані такі наукові методи, як метод аналізу, метод синтезу, методи індукції та метод дедукції, та спеціально правові методи дослідження, як юридично-догматичний методі та метод тлумачення правових норм. Автори прийшли до наступних висновків. По-перше, статті 387 та 391 ЦК слід доповнити назвами віндикаційного і негаторного позовів. Крім того, потребує вирішення проблема конкуренції віндикації, реституції та кондикції, закладена у ст. 1212 ЦК. По-друге, варто більш чітко викласти механізм переведення прав та обов’язків покупця. По-третє, є необхідність удосконалення інституту набувальноїдавності за цивільним законодавством України.
Safonchyk O. Current Issues of Recodification of Civil Legislation of Ukraine in the Context of European Integration Processes / O. Safonchyk, K. Hlyniana, R. Ennan // Amazonia Investiga. – Vol. 9. – Iss. 28. – Editorial Primmate S. A. S., 2020. – P. 303-310.
Keywords: recodification; civil law; legal norm; European integration; legal institute; рекодифікація; цивільне законодавство; правова норма; євроінтеграція; правовий інститут; Research Subject Categories::LAW/JURISPRUDENCE